Effect of Modified Atmosphere Packaging on the Physical and Microbiological Properties of Shucked Fresh Oyster - ธีระวุฒิ สวามินี; พิมพ์แน่น รัตนาภรณ์; เมืองฮาม โสภาวดี (KKU Science Journal, 2014)
The purpose of this study was to investigate effect of modified atmosphere packaging on the physical and microbiological properties of shucked fresh oyster (Saccostrea cucullata) in mixed solution (3% potassium sorbate and 2.5% sodium lactate). The shucked fresh oysters were packed in five different treatment conditions (T1 – T5) which T1 (40%CO2:20%O2:40%N2),T2 (40%CO2:30%O2:30%N2), T3 (60%CO2:20%O2:20%N2), T4 (60%CO2:40%O2) and T5 (atmosphericair), respectively and stored at 4±1 ºC. The results showed that the shucked fresh oysters which were packed under T3 condition had the lowest changes refer the criteria of physical and microbiological properties.The shucked fresh oyster packed in T3 had shelf–life of storage for 10 days (total plate count not exceeded log 6 cfu/g). The shucked fresh oyster packed in T4, T2 and T1 were 9, 7 and 6 days, respectively compared with shucked fresh oyster kept in T5 (atmospheric air) which had the shortest shelf–life only 5 days.